2018
DOI: 10.1029/2018gl079232
|View full text |Cite
|
Sign up to set email alerts
|

Magnetosonic Harmonic Falling and Rising Frequency Emissions Potentially Generated by Nonlinear Wave‐Wave Interactions in the Van Allen Radiation Belts

Abstract: Magnetosonic waves play a potentially important role in the complex evolution of the radiation belt electrons. These waves typically appear as discrete emission lines along the proton gyrofrequency harmonics, consistent with the prediction of the local Bernstein mode instability of hot proton ring distributions. Magnetosonic waves are nearly dispersionless particularly at low harmonics and therefore have the roughly unchanged frequency time structures during the propagation. On the basis of Van Allen Probes ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 60 publications
0
28
0
Order By: Relevance
“…To determine the combined effect of different factors on the EMIC instabilities, we calculate the linear growth rates of parallel‐propagating waves using our previously developed code (Liu et al, 2018a, 2018b; Su et al, 2018). The expressions for the spatial K i and temporal γ growth rates can be written as (Chen et al, 2010; Kennel, 1966; Kennel & Petschek, 1966) Knormali=γfalse/false|boldvgfalse|, γ=1Dω4πe2ε0mnormalHPfalse(RLfalse)ω2NnormalR·)(AnormalRAnormalC, NnormalR=2πnormalΩnormalHωk·0vdvFtrue|vfalse‖=vnormalR,0.1em AnormalR=0vdv)(vfalse‖FvvFvfalse‖vv<...>…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…To determine the combined effect of different factors on the EMIC instabilities, we calculate the linear growth rates of parallel‐propagating waves using our previously developed code (Liu et al, 2018a, 2018b; Su et al, 2018). The expressions for the spatial K i and temporal γ growth rates can be written as (Chen et al, 2010; Kennel, 1966; Kennel & Petschek, 1966) Knormali=γfalse/false|boldvgfalse|, γ=1Dω4πe2ε0mnormalHPfalse(RLfalse)ω2NnormalR·)(AnormalRAnormalC, NnormalR=2πnormalΩnormalHωk·0vdvFtrue|vfalse‖=vnormalR,0.1em AnormalR=0vdv)(vfalse‖FvvFvfalse‖vv<...>…”
Section: Physical Mechanismsmentioning
confidence: 99%
“…Perraut et al (1982) found that nonlinear sum-frequency interactions can occur between magnetosonic branches in the first harmonic and produce higher harmonic structures, which is analogous to the situation of the second event. Recently, Liu et al (2018) reported nonlinear difference-frequency interactions between locally generated magnetosonic waves and a propagating magnetosonic wave. Our results, together with previous studies, provide a comprehensive picture of the nonlinear interactions of Bernstein-mode waves.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there has been a resurgence of interest in the nonlinear wave‐wave interactions within the magnetosphere. Three‐wave resonances are invoked to explain the multibanded or highly oblique whistler waves (Agapitov et al, ; Fu et al, ; Gao et al, ; Teng et al, ; Vasko et al, ) and the magnetosonic harmonic falling/rising frequency waves (Liu et al, ). Here we present the first evidence for the nonlinear coupling between chorus and ECH waves and highlight the energy redistribution among the resonant waves.…”
Section: Discussionmentioning
confidence: 99%